Regression modeling of combined sewer overflows to assess system performance - Matthew A. Bizer; Christine J. Kirchhoff (Water Science and Technology, 2022)
Combined sewer overflows (CSOs) occur when untreated raw sewage mixed with rainwater, runoff, or snowmelt is released during or after a storm in any community with a combined sewer system (CSS). Climate change makes CSOs worse in many locales; as the frequency and severity of wet weather events increases, so do the frequency and volume of CSO events. CSOs pose risks to humans and the environment, and as such, CSS communities are under regulatory pressure to reduce CSOs. Yet, CSS communities lack the tools needed, such as performance indicators, to assess CSS performance. Using the city of Cumberland, Maryland as a case study, we use public data on CSOs and precipitation over a span of 16 years to identify a new critical rainfall intensity threshold that triggers likely CSO incidence, and a multiple linear regression model to predict CSO volume using rainfall event characteristics. Together, this indicator and modeling approach can help CSS communities assess the performance of their CSS over time, especially to evaluate the effectiveness of efforts to reduce CSOs. HIGHLIGHTS Rainfall events in two watersheds are sorted by single-hour maximum intensity (mm/h) to identify a CSO incidence threshold.; The critical intensity threshold (Icrit), a novel indicator of CSS performance independent of rainfall measurements, is developed.; A multiple linear regression model is developed that predicts CSO volumes from the depth and average intensity of the associated rainfall event.; The two-pronged approach of Icrit and the multiple regression model serve as new performance indicators to assess CSS performance under changing precipitation, and relatively unchanging conditions of urbanization and population.;